C-Reactive Protein Concentrations Among Crop and Dairy Farmers with Stable Chronic Obstructive Pulmonary Disease - Saso Stoleski; Jordan Minov; Jovanka Karadzinska-Bislimovska; Dragan Mijakoski; Lütfiye Tutkun (ID Design 2012/DOOEL Skopje, Republic of Macedonia, 2017)
AIM: To assess the mean serum C-reactive protein concentrations among farmers and office controls, and further examined its relation to exposure duration, smoking habit, as well as presence or absence of COPD. METHODS: A cross-sectional survey was performed including examined group (EG), composed of agricultural workers (87 crop - EG1 and 83 dairy farmers - EG2), and control group (CG) composed by 80 office workers. Evaluation of subjects included a questionnaire on chronic respiratory symptoms, lung function tests, COPD diagnostics, and measurement of CRP serum concentrations. RESULTS: Serum CRP concentrations were raised in stable COPD patients independent of smoking habit or exposure duration. The mean CRP serum concentrations were higher in the subjects of EG1 and EG2 compared with those in CG, but without statistical significance. This count for mean CRP serum concentrations in subjects of EG1 and EG2 exposed more than 20 years and for those in smokers in all three groups as well. The mean CRP serum concentrations were significantly higher in subjects with COPD within EG1 (P=0.049) and EG2 (P=0.040), while those in CG were not. CONCLUSION: Data obtained suggest that systemic inflammation is present in farmers with COPD and CRP is an important biomarker in COPD in means of reflecting disease severity and prognosis of exposed farmers.
Keywords: markers of inflammation; COPD; farmers; respiratory symptoms; spirometry